Fast 3D Isotropic Proton Density-Weighted Fat-Saturated MRI of the Knee at 1.5 T with Compressed Sensing: Comparison with Conventional Multiplanar 2D Sequences - Endler, Christoph H.-J.; Faron, Anton; Isaak, Alexander; Katemann, Christoph; Mesropyan, Narine; Kupczyk, Patrick A.; Pieper, Claus C.; Kuetting, Daniel; Hadizadeh, Dariusch R.; Attenberger, Ulrike I.; Luetkens, Julian A. (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2021)
Purpose Compressed sensing (CS) is a method to accelerate MRI acquisition by acquiring less data through undersampling of k-space. In this prospective study we aimed to evaluate whether a three-dimensional (3D) isotropic proton density-weighted fat saturated sequence (PDwFS) with CS can replace conventional multidirectional two-dimensional (2D) sequences at 1.5 Tesla.Materials and Methods 20 patients (45.2 ± 20.2 years; 10 women) with suspected internal knee damage received a 3D PDwFS with CS acceleration factor 8 (acquisition time: 4:11 min) in addition to standard three-plane 2D PDwFS sequences (acquisition time: 4:05 min + 3:03 min + 4:46 min = 11:54 min) at 1.5 Tesla. Scores for homogeneity of fat saturation, image sharpness, and artifacts were rated by two board-certified radiologists on the basis of 5-point Likert scales. Based on these ratings, an overall image quality score was generated. Additionally, quantitative contrast ratios for the menisci (MEN), the anterior (ACL) and the posterior cruciate ligament (PCL) in comparison with the popliteus muscle were calculated.Results The overall image quality was rated superior in 3D PDwFS compared to 2D PDwFS sequences (14.45 ± 0.83 vs. 12.85 ± 0.99; p < 0.01), particularly due to fewer artifacts (4.65 ± 0.67 vs. 3.65 ± 0.49; p < 0.01) and a more homogeneous fat saturation (4.95 ± 0.22 vs. 4.55 ± 0.51; p < 0.01). Scores for image sharpness were comparable (4.80 ± 0.41 vs. 4.65 ± 0.49; p = 0.30). Quantitative contrast ratios for all measured structures were superior in 3D PDwFS (MEN: p < 0.05; ACL: p = 0.06; PCL: p = 0.33). In one case a meniscal tear was only diagnosed using multiplanar reformation of 3D PDwFS, but it would have been missed on standard multiplanar 2D sequences.Conclusion An isotropic fat-saturated 3D PD sequence with CS enables fast and high-quality 3D imaging of the knee joint at 1.5 T and may replace conventional multiplanar 2D sequences. Besides faster image acquisition, the 3D sequence provides advantages in small structure imaging by multiplanar reformation.Key Points: Citation Format
Keywords: 3D sequence; knee imaging; MRI; meniscal tear; compressed sensing